An integrated e-learning system for simulation-based instruction of anaesthesia machines. (27th February 2007) - Jeon, Sanghyun S.; Lee, Gilliean; Lampotang, Samsun (Sem); Su, Stanley Y.W.
Not all learners learn in the same way and at the same rate. Learners' learning styles that reflect their cognitive abilities vary in known ways; some prefer the traditional text-based or oral presentation of content, while others learn more easily in a visual or kinaesthetic instruction style. Simulation has been shown to be an effective way of teaching abstract concept, principle and process in many application domains. In this paper, we have developed reusable, interactive, simulation-based learning objects and designed and implemented an e-learning system called Gator E-learning System (GELS), to deliver the learning objects to learners in an interactive, adaptive and flexible manner. GELS integrates a web-based Virtual Anaesthesia Machine (VAM) Simulation System and a Collaborative and Dynamic E-learning Service System (CoDESS) for the purpose of teaching medical personnel the functions and operations of anaesthesia machines as well the preuse check of anaesthesia machines in a simulation-based learning environment.